Twitter Discourse Analysis of US President Donald Trump - Tasente, Tanase (Technium Social Sciences Journal, 2021)
Twitter has become a very powerful channel of political communication in recent years, many times overtaking, along with Facebook, traditional channels of mass communication, such as: TV, radio or newspapers. More then 500 million tweets are sent every day (5,787 tweets every second), and 326 million people use Twitter every month, even if there are 1.3 billion Twitter accounts. From the perspective of political communication, Twitter is ahead of Facebook, according to a study conducted in 2018 by Twiplomacy, which shows that 187 governments and heads of state maintain an official presence on Twitter. This mechanism of mass communication has benefited the politicians, especially those in the United States of America, who have generated a unique phenomenon in political communication: creating a map on polarization in the online environment.. This study focused on analyzing the Key Performance Indicators (KPIs) that facilitate Twitter Communication of Donald Trump, the President of United States of America (number of followers, types of tweets, engagement rate and interaction rate etc.) and analyzing Donald Trump's Twitter speech and identify the most commonly used expressions in Social Media during the term of President. The monitoring period is 22.01.2019 - 16.08.2019.